The AnalysÄ±s of Technology Acceptance Model (Tam) on Consumer Loyalty of Travelokapay Payment Systems in Travelokaeats ServÄ±ces - Gardian, Hardy; Kusumawardhana, Indra; Sari, Nabilah Fadiyah; Mustikasari, Faranita (APMBA (Asia Pacific Management and Business Application), 2022)
The massive technology development introduce non cash payment method using mobile phone, namely mobile payment. It changes consumer behaviour in conduct transaction and specifically induced by COVID 19 pandemic situation, whereas consumer minimize cash transaction. In Indonesian online travel provider, there are various brands available, and Travelokapay in TravelokaEats application considered as the new player in the market. Consumer may not easily adopt a new technology, because of various factors. This study aims to determine the effect of perceived of ease of use and usefulness on consumer attitudes which influence consumer interest in continuing to use the TravelokaPay payment system on the TravelokaEats service. It uses Technology Acceptance Model (TAM) which recognized as the familiar approach for new technology adoption. Data gathered from 158 respondents reside in Jakarta, Indonesia with purposive sampling technique. Analysis is conducted using Partial Least Square Structural Equation Modelling (PLS SEM). The results demonstrate that perceived ease of use significantly affect perceived usefulness, consumer attitude and continutaion intention. While perceived usefulness significantly affect only to consumer attitude.